2021
DOI: 10.1002/cac2.12153
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant immunotherapy for non–small cell lung cancer: State of the art

Abstract: Lung cancer mortality has decreased over the past decade and can be partly attributed to advances in targeted therapy and immunotherapy. Immune checkpoint inhibitors (ICIs) have rapidly evolved from investigational drugs to standard of care for the treatment of metastatic non‐small cell lung cancer (NSCLC). In particular, antibodies that block inhibitory immune checkpoints, such as programmed cell death protein 1 (PD‐1) and programmed cell death 1 ligand 1 (PD‐L1), have revolutionized the treatment of advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 106 publications
0
76
0
5
Order By: Relevance
“…Patients with non-small-cell lung cancer (NSCLC) most often present with inoperable, locally advanced or metastatic disease for which no cure is available [2,3]. Although survival has improved significantly in recent years with the introduction of kinase inhibitors and immune checkpoint inhibitors, the 5-year survival rate is still only about 25% [1,4,5]. The standard of care for patients with NSCLC varies with the stage of the disease at diagnosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with non-small-cell lung cancer (NSCLC) most often present with inoperable, locally advanced or metastatic disease for which no cure is available [2,3]. Although survival has improved significantly in recent years with the introduction of kinase inhibitors and immune checkpoint inhibitors, the 5-year survival rate is still only about 25% [1,4,5]. The standard of care for patients with NSCLC varies with the stage of the disease at diagnosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite progress in the use of targeted therapies, the optimism arising from their application has been tempered by inconsistent responses to these therapies and the emergence of drug resistance in many patients [4]. Progress in SCC treatments has been modest, and targeted therapy in this disease has not yet been proven successful [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the multivariate analysis, it was shown that immunotherapy employed as a second or more line of therapy was significantly correlated to a better response rate. We can speculate that this finding could be associated with the growing evidence that cytotoxic chemotherapy and radiotherapy could impact tumor ligand expression, determining changes in cell PD-L1 expression as well as in the tumor microenvironment [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 94%